Valutazione economica dello studio CARDS: un aggiornamento - de Portu, Simona; Montella, Sabato; Cortesi, Paolo; Menditto, Enrica; Mantovani, Lorenzo G. (Farmeconomia. Health economics and therapeutic pathways, 2011)
Introduction: in the last decades, prevalence and incidence of type II diabetes mellitus have been rapidly growing worldwide. Most recent projections estimate that the number of people affected by diabetes is destined to double in 2030, producing a significant increase of the healthcare expenditure for the management of complications. Prevention of cardiovascular events in diabetes population represents a priority for decision makers, who have to evaluate the cost-effectiveness of therapeutic interventions. Objective: to provide an updated cost-effectiveness evaluation of treating type II diabetes patients with atorvastatin versus placebo, in the light of the imminent price reduction of atorvastatin due to loss of exclusivity and of other therapeutic and hospital costs. Material and Methods: we derived clinical information from the CARDS study, a randomized, multicenter clinical trial evaluating efficacy of atorvastatin versus placebo in preventing the occurrence of cardiovascular events in a cohort of type II diabetes patients without previous history of coronary events. A cost-effectiveness analysis in the perspective of the National Healthcare System (SSN) has been performed, under the hypothesis of the imminent price reduction of atorvastatin, due to the loss of exclusivity. Results: after a median follow up of 3.9 years, the number of patients with at least a major cardiovascular event requiring hospitalization was lower in the atorvastatin arm (5.8%) compared to the placebo arm (9.0%; p=0.001). Based on a cohort of 1,000 patients, treatment with atorvastatin permitted to gain 29.28 life years. The incremental cost of adding atorvastatin to the standard therapy amounted to €305,682, and was partially balanced by a cost reduction due to fewer hospitalizations, compared to the placebo arm (€ 168,313). Total direct costs were of €602.186 in the atorvastatin group and of € 464,818 in the placebo group, resulting into an incremental cost-effectiveness ratio of € 4,692 for Life Year Gained (LYG). Conclusion: the present study is an update of a previous economic analysis of the CARDS trial. Under the assumed new cost scenario, the cost-effectiveness profile of treating diabetic patients with atorvastatin becomes highly favourable, and leads to a significant reduction of the cost for Life Year Gained compared to the previous findings.